Durum wheat cultivation and breeding in the Altai Russian region - Rozova M.A.; Pocornyak V.P. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Altai territory is the third – fourth largest durum producer in Russia as a whole. Durum wheat appeared on the territory at the middle of 19th century. From the first steps durum appeared to be good yielder under varying sowing area: 3 000 ha after World War II till 400 000 ha at the end of stagnation time. Breeding work was initiated in 1929 and since 1970 it is incessant. Peculiar Siberian climate calls for specially adapted varieties. Since 1970 8 varieties of durum wheat have been released. Breeding progress in grain productivity made up 44%. At present major challenges are: (i) high and stable yield through good adaptation to abiotic (moisture deficit, heat stress) and biotic (loose smut, Septoria tritici blotch, common root rot, black point, ergot, sawfly, cereal leaf beetle and others) stresses; (ii) improvement of quality parameters – protein content, gluten content and quality, kernel vitreousness, semolina color, cooking strength, firmness of pasta; (iii) resistance to lodging (traditional type with strong culm); (iv) ease of threshing and some other. For the development of new genetic diversity inter- (Triticum aestivum, T.dicoccum, T. turgidum, T.timopheevii, T. persicum, T.monococcum, T.bioticum, T.turanicum in descending order) and intraspecies hybridization is used.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)